The Use of Gesture in Improving Students’ Vocabulary Mastery in Selected Indonesian Junior High School - Indrayani Simpuruh (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
This presents research explore on the use of gestures to improve students’ vocabulary mastery at the second grade students of Indonesian junior high school. This quantitative research involved 60 students as its sample. The data obtained from the pretest, treatments, and posttest were were analysed to find its mean score and the score of t-test. The result of the study showed that there was a significant improvement of the students’ achievement after giving the treatment. The data shows that the t-test obtained by the students (16.28) is greater than t-table (2.045). This is means that H0 is rejected and H1 is acceptable. The data of students’ interest which were taken by using questionnaire shows that 25 students (83.33%) are in the very high category and left only five students (16.67%) in the high category. It means that the students were interested and this technique is suitable in teaching English vocabulary.